2017
DOI: 10.1002/hed.25049
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐aided system for diagnosing thyroid nodules on ultrasound: A comparison with radiologist‐based clinical assessments

Abstract: The sensitivity of a thyroid ultrasound CAD system in differentiating nodules was similar to that of an experienced radiologist. However, the CAD system had lower specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 13 publications
(30 reference statements)
5
62
3
Order By: Relevance
“…The pooled sensitivity, specificity, AUC, and DOR are demonstrated in Figure 2b. Eleven of the 13 studies compared the diagnostic performances of CAD systems and radiologists [7,20,21,[23][24][25][26][27][28]. The pooled sensitivity, specificity, AUC, and DOR were comparable between the CAD systems and the radiologists (Fig.…”
Section: Diagnostic Performance Of Deep Learning-based Cad Systemsmentioning
confidence: 94%
See 2 more Smart Citations
“…The pooled sensitivity, specificity, AUC, and DOR are demonstrated in Figure 2b. Eleven of the 13 studies compared the diagnostic performances of CAD systems and radiologists [7,20,21,[23][24][25][26][27][28]. The pooled sensitivity, specificity, AUC, and DOR were comparable between the CAD systems and the radiologists (Fig.…”
Section: Diagnostic Performance Of Deep Learning-based Cad Systemsmentioning
confidence: 94%
“…The flow diagram of the literature search is shown in Figure 1. Nineteen studies with 4,781 nodules used in external validation sets were included in the study, including 6 studies on classic machine learning-based CAD sys-DOI: 10.1159/000504390 tems [14][15][16][17][18][19] and 13 studies on deep learning-based CAD systems [7,[20][21][22][23][24][25][26][27][28][29][30][31]. The general characteristics of the included studies are shown in Table 1, and the detailed characteristics are demonstrated in online supplementary Table 1 (see www.karger.com/doi/10.1159/000504390 for all online suppl.…”
Section: Literature Searches and Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies of CAD systems based on deep learning algorithms have consistently observed high sensitivity and low specificity, especially for studies with small sample sizes. For instance, in a retrospective study that developed a CNN model using 342 cases of thyroid nodules, the sensitivity, specificity, PPV, NPV, accuracy, and AUC of the CNN model were 96.7%, 48.5%, 87.3%, 86.2%, 82.2%, and 0.73, respectively, compared with values of 96.2%, 75.7%, 90.2%, 89.7%, 90.1%, and 0.87, respectively, for 2017 ACR TI-RADS [19]. Another study compared the deep learning system with the Automated Breast Ultrasound (ABUS) based on BI-RADS [20].…”
Section: Discussionmentioning
confidence: 96%
“…Most image datasets used for training only included fewer than 200 thyroid nodules. Gao 25 used a computer-aided system that was based on multiple-scale CNN model and trained by a large ultrasound image dataset with 1700 benign nodules and 2000 malignant nodules. The sensitivity of their CAD system was similar to that of an experienced radiologist.…”
Section: Discussionmentioning
confidence: 99%